2010
DOI: 10.1021/ef901130q
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Recovery from Fermentation Broth via Carbon Dioxide Stripping and Adsorption

Abstract: With the depletion of fossil fuels, research in alternative energy sources that can provide the world's energy demand has increased significantly during the past decade. One alternative energy source in particular that has gained worldwide recognition as a potential replacement to oil is bioethanol. It is renewable and environmentally friendlier than fossil fuels. In this study, adsorption is used to increase the efficiency of ethanol production by decreasing the effect of product inhibition using carbon dioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
1
23
0
2
Order By: Relevance
“…It is therefore necessary to conduct further research in order to check the influence of other components on adsorption, or to investigate other methods that can be coupled with adsorption to facilitate the separation and purification of ethanol. Some of the methods that can be used with adsorption are ozonation ( 178 , 179 ) or gas stripping ( 180 , 181 ). …”
Section: Bioethanol Separation and Purificationmentioning
confidence: 99%
“…It is therefore necessary to conduct further research in order to check the influence of other components on adsorption, or to investigate other methods that can be coupled with adsorption to facilitate the separation and purification of ethanol. Some of the methods that can be used with adsorption are ozonation ( 178 , 179 ) or gas stripping ( 180 , 181 ). …”
Section: Bioethanol Separation and Purificationmentioning
confidence: 99%
“…This process option avoids the circulation of fermentation broth through the membrane unit thereby avoiding membrane fouling and additionally utilizes the fermentation byproduct, CO2, which otherwise is mostly vented-off from the process. Ethanol stripping from fermentation broth by CO2 and recovery by different separation techniques, such as adsorption, rectification and condensation, has been successfully demonstrated [15][16][17]. To our knowledge, this is the first report proposing the above mentioned process option.…”
Section: Introductionmentioning
confidence: 92%
“…Activated carbon is the most commonly used ethanol adsorbent. Hashi et al [71] compared four activated carbon adsorbents (Sorbonorit B4, Filtrasorb 200, WV-B 1500 and Nuchar RGC 40) and two hydrophobic ZSM-5-type zeolites (HiSiv 3000 and CBV 8014), it was found that activated WV-B 1500 has the highest ability to adsorb ethanol, and activated carbons showed higher ethanol adsorption ability than the two zeolites. Despite different types of adsorbents has been reported as a potential adsorbent for ethanol recovery, the majority of the reported works used ethanol/water, ethanol/glucose or ABE mixture models during the investigation [72][73][74][75][76][77][78][79].…”
Section: Adsorptionmentioning
confidence: 99%